Misguided transcriptional elongation causes mixed lineage leukemia - Mueller, Dorothee; Garcia-Cuellar, Maria-Paz; Bach, Christian; Buhl, Sebastian; Mäthner, Emanuel; Slany, Robert (Plos Biology, 2009)
Fusion proteins composed of the histone methyltransferase mixed-lineage leukemia (MLL) and a variety of unrelated fusion partners are highly leukemogenic. Despite their prevalence, particularly in pediatric acute leukemia, many molecular details of their transforming mechanism are unknown. Here, we provide mechanistic insight into the function of MLL fusions, demonstrating that they capture a transcriptional elongation complex that has been previously found associated with the eleven-nineteen leukemia protein (ENL). We show that this complex consists of a tight core stabilized by recursive protein-protein interactions. This central part integrates histone H3 lysine 79 methylation, RNA Polymerase II (RNA Pol II) phosphorylation, and MLL fusion partners to stimulate transcriptional elongation as evidenced by RNA tethering assays. Coimmunoprecipitations indicated that MLL fusions are incorporated into this complex, causing a constitutive recruitment of elongation activity to MLL target loci. Chromatin immunoprecipitations (ChIP) of the homeobox gene A cluster confirmed a close relationship between binding of MLL fusions and transcript levels. A time-resolved ChIP utilizing a conditional MLL fusion singled out H3K79 methylation as the primary parameter correlated with target expression. The presence of MLL fusion proteins also kept RNA Pol II in an actively elongating state and prevented accumulation of inhibitory histone methylation on target chromatin. Hox loci remained open and productive in the presence of MLL fusion activity even under conditions of forced differentiation. Finally, MLL-transformed cells were particularly sensitive to pharmacological inhibition of RNA Pol II phosphorylation, pointing to a potential treatment for MLL. In summary, we show aberrant transcriptional elongation as a novel mechanism for oncogenic transformation. © 2009 Mueller et al.